Biallelic germline MBD4 mutations predispose to colorectal polyposis, hypermutated AML, and schwannomas - Julia Cooper; Brittany L. Stewart; Lauren Bokovitz; Hetty Carraway; Sudipto Mukherjee; David Liska; Sumithira Vasu; Harry Lesmana; James S. Blachly (Familial Cancer, 2026)
Biallelic pathogenic variants in the MBD4 gene have recently been associated with an autosomal recessive cancer predisposition syndrome deemed “ MBD4 -associated neoplasia syndrome (MANS)”. Early reports of individuals with MANS highlight the propensity to develop young onset colorectal polyposis and hyper-mutated acute myeloid leukemia (AML). In the following case series, we present four patients with MANS from three families with polyps and AML, as well as additional features previously less described, such as schwannoma and thyroid cancer. This series increases the total number of reported cases by 27%, with the intention of achieving a more robust understanding of the full phenotypic spectrum of MANS.